Plasmonic Waveguides with Properties and Applications: A Review - Jitender; Pahuja, Poonam (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 2), 2024)
Plasmonics due to its applications and analogy with other branches of science is considered as multidisciplinary in nature leading researchers of different fields, such as applied physics, sensing, optoelectronics, chemistry, biomedical sciences, etc., exploiting it for potentially high-speed futuristic miniaturized devices. In this chapter, we have discussed the type of plasmons and plasmonic waveguides that have been considered by different people exploring their properties for a wide range of applications.